1982
DOI: 10.1159/000172833
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in the Term Pregnant Rat: A Micropuncture Study

Abstract: The purpose of this study was to define individual nephron function and salt and fluid reabsorption in the term pregnant rat utilizing standard micropuncture techniques. The studies were performed at the time of maximal sodium retention and when extracellular fluid volume was significantly increased. During micropuncture in 7 pregnant and 9 non-pregnant rats, we found no difference, respectively, in GFR 1.04 + 0.06 vs. 1.13 ± 0.06 ml/min/kidney or nephron GFR 35 ± 0.9 vs. 33 ± 1 ml/min. Fractional and absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In midand late-gestation increased sodium and water reabsorption were observed in loops of Henle (Garland & Green, 1982;Green & Hatton, 1987) and in nephron sites distal to early distal convoluted tubules (Garland & Green, 1982;Arthur & Green, 1986). In contrast, Churchill, Bengele & Alexander (1982) were unable to demonstrate altered proximal and loop of Henle sodium reabsorption in late-pregnant rats.…”
Section: Introductionmentioning
confidence: 78%
“…In midand late-gestation increased sodium and water reabsorption were observed in loops of Henle (Garland & Green, 1982;Green & Hatton, 1987) and in nephron sites distal to early distal convoluted tubules (Garland & Green, 1982;Arthur & Green, 1986). In contrast, Churchill, Bengele & Alexander (1982) were unable to demonstrate altered proximal and loop of Henle sodium reabsorption in late-pregnant rats.…”
Section: Introductionmentioning
confidence: 78%
“…GFR is increased by 50-80% through most of pregnancy in women [108,239,503]. Although changes in kidney weight, if any, during pregnancy are unknown [293], glucose Tm is not increased [92,502], In the rat GFR and ERPF are increased by 20-30% during the last half of pregnancy [26,27,41,93,100,109,175,292], Similar changes were also seen in the pseudopregnant rat [42]. Although wet weight is increased early in rat [109] and mouse [337], no changes in dry weight have been found [109].…”
Section: Thermodynamic Workmentioning
confidence: 99%
“…Thus, factors such as the method and degree of body fluid volume expansion employed, measurements being made during non-steady-state conditions, and the extent of the anaesthesia/surgery employed may be important. In this respect, Churchill, Bengele & Alexander (1982) demonstrated that g.f.r. in term-pregnant rats prepared for micropuncture was similar to that in virgin controls, whereas in anaesthetized non-micropunctured term-pregnant animals g.f.r.…”
Section: Introductionmentioning
confidence: 98%